Trends in Atmospheric Nitrogen Deposition in Macedonia Studied by Using the Moss Biomonitoring Technique - Katerina Bačeva Andonovska, Trajče Stafilov, Robert Šajn, Biljana Jordanoska Shishkoska, Valentina Pelivanoska, Lambe Barandovski (MDPI, 2024)
This study examined the nitrogen content in moss samples collected across Macedonia over a 15-year period (2005, 2010, 2015 and 2020) from 72 consistent sampling locations. The nitrogen content was determined using the Kjeldahl method, providing insight into the trends of atmospheric nitrogen deposition across different regions. Descriptive statistical analyses, including spatial distribution maps, were used to compare the temporal variations and regional nitrogen levels. In addition, box-plots (P25–P75) and whiskers (P5–P95) were constructed to provide a comprehensive view of the variability across different tectonic units and zones, allowing for an in-depth understanding of the spatial distribution of nitrogen across the country. The study revealed that the median nitrogen content in moss samples decreased from 1.21% in 2005 to 1.04% in 2015, followed by a slight increase to 1.07% in 2020. The highest nitrogen concentrations were consistently found in areas with heavy agricultural activities and high traffic volumes, indicating the direct impact of these anthropogenic factors. The comparisons across regions and geological zones also highlighted the substantial variation in nitrogen levels, reflecting the diverse environmental pressures in different parts of Macedonia. This long-term analysis not only offers valuable insights into the trends in nitrogen pollution but also underlines the necessity for targeted policy interventions, particularly in the regions where nitrogen levels remain persistently high.
Keywords: nitrogen; air pollution; moss biomonitoring; Kjeldahl method; Macedonia